Faculty perception of practices and skills for undergraduate assessment in a medical college in Karnataka -a cross- sectional study - Teli Chandrika,; N.Ananthakrishnan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Assessment of students' proficiency is seen as a crucial duty of every teacher. A variety of assessment methods and instruments are necessary to evaluate diverse abilities, particularly complicated attributes such as ethics, professionalism, and lifelong learning. Yet, little is known about faculty attitudes regarding different aspects of assessment and self-perception about their skills required for assessment. These have wide-ranging implications for students, faculty and policy in institutions. This study was conducted to know the existing practices and self -perceived expertise of faculty in undergraduate assessments. This knowledge would serve a guide for recommendations and policy changes in the institute Aim :To study perception of faculty about undergraduate assessments practices and self -perceived skills for the same. Materials And Methods: A cross sectional study was conducted in Esic Medical College Gulbarga, Karnataka, India from July 23 to June 24. Using google form and a convenience sampling method, present study investigated the perceptions of 80 faculty of teaching experience more than 1 year, involved in assessment of undergraduate students. The questionnaire composed of sections as demographic data, perception of different aspects of formative assessment, practices regarding assessment tools and self-perception of mastery of skills of assessment. A 2 × 2 multivariate analysis of variance was used to analyze the data teaching experience as independent variables and self-perceived assessment skills and practices as dependent variables. Results: Results. 90% faculty participated in CPD, but majority did not use new assessment tools in practice in 2 academic years.Though teachers with 5-10 years of experience showed higher mean in assessment practices in all domains.No significant difference was observed for skills practices [p=0.089 for cognitive ,p=0,029 for psychomotor and p=0.34 for affective domain assessment]. Teachers with over 15 years of experience reported higher mean on self-perceptions of mastery in assessment skills, which was statistically significant [p=0.000]. Conclusion: Medical instructor training has led to improved cooperation and a positive shift in faculty attitudes toward newer assessment tools, these changes have not been fully implemented. A comprehensive Faculty Development Program with monitoring is needed for sustained local impact.